A qualitative inquiry of rural-urban inequalities in the distribution and retention of healthcare workers in southern Nigeria. - Ogonna N O Nwankwo; Chukwuebuka I Ugwu; Grace I Nwankwo; Michael A Akpoke; Collins Anyigor; Uzoma Obi-Nwankwo; Sunday Andrew; Kelechukwu Nwogu; Neil Spicer (PLoS ONE, 2022)
Introduction Globally, the population in rural communities are disproportionately cared for by only 25% and 38% of the total physicians and nursing staff, respectively; hence, the poor health outcomes in these communities. This condition is worse in Nigeria by the critical shortage of skilled healthcare workforce. This study aimed to explore factors responsible for the uneven distribution of healthcare workers (physicians and nurses) to rural areas of Ebonyi State, Nigeria. Methods Qualitative data were obtained using semi-structured in-depth interviews and focus group discussions from purposively selected physicians, nurses, and policymakers in the state. Data was analysed for themes related to factors influencing the mal-distribution of healthcare workers (physicians and nurses) to rural areas. The qualitative analysis involved the use of both inductive and deductive reasoning in an iterative manner. Results This study showed that there were diverse reasons for the uneven distribution of skilled healthcare workers in Ebonyi State. This was broadly classified into three themes; socio-cultural, healthcare system, and personal healthcare workers' intrinsic factors. The socio-cultural factors include symbolic capital and stigma while healthcare system and governance issues include poor human resources for health policy and planning, work resources and environment, decentralization, salary differences, skewed distribution of tertiary health facilities to urban area and political interference. The intrinsic healthcare workers' factors include career progression and prospect, negative effect on family life, personal characteristics and background, isolation, personal perceptions and beliefs. Conclusions There may be a need to implement both non-financial and financial actions to encourage more urban to rural migration of healthcare workers (physicians and nurses) and to provide incentives for the retention of rural-based health workers.